Analisis Perbandingan Sistem Pakar dalam Mendiagnosa Penyakit Limfoma Hodgkin Menggunakan Algoritma Teorema Bayes dan Certainty Factor - Mahendra, Muklis; Pane, Rahmadhani; Rohani, Rohani (Forum Kerjasama Pendidikan Tinggi, 2023)
Disease is a major challenge in the medical world. Accurate and timely diagnosis is a crucial key in disease management, including in cases of cancer. One type of cancer that affects the lymphatic system in the body is Hodgkin's lymphoma, which is also considered a rare disease. Typically, this disease occurs in adolescents and adults. Hodgkin's lymphoma requires serious treatment, although there are also cases of successful recovery. The importance of accurate and timely diagnosis in diagnosing Hodgkin's lymphoma is a critical factor in planning effective treatment and providing a favorable prognosis for patients. This study aims to perform a comparative evaluation of the Bayesian Theorem and Certainty Factor methods in diagnosing Hodgkin's lymphoma by comparing both methods. Diagnosing this disease is challenging for an expert due to the similarity of symptoms with other lymphoma diseases, which adds complexity. Therefore, this research provides an alternative to facilitate diagnosis by utilizing a system that can determine the level of certainty of a disease based on available data, including symptoms, expert values, and user values. After conducting research by comparing the two algorithms, Bayesian Theorem and Certainty Factor, various processing stages were implemented according to the established algorithm. The Bayesian Theorem algorithm yielded a result of 77.7%, while the Certainty Factor algorithm produced a higher value of 94.1%. The comparison between the Bayesian Theorem and Certainty Factor methods shows that the Certainty Factor method is more accurate in diagnosing Hodgkin's lymphoma and can be used in further research